An unfinished life : John F. Kennedy, 1917-1963 - Dallek, Robert (Boston : Little, Brown, and Co., 2003)
An unfinished life is the first major, single-volume life of John F. Kennedy to be written by a historian in nearly four decades. Robert Dallek draws upon previously unavailable material and never-before-opened archives to tell Kennedy's story. We learn just how sick Kennedy was, what medications he took and concealed from all but a few, and how severely his medical condition affected his actions as President. We also learn the real story of how Bobby was selected as Attorney General. Dallek reveals exactly what Jack's father did to help his election to the presidency, and he follows previously unknown evidence to show what path JFK would have taken in the Vietnam entanglement had he survived. Dallek shows that while Kennedy was the son of privilege, he faced great obstacles and fought on with remarkable courage. Never shying away from Kennedy's weaknesses, Dallek also explores his strengths. The result is a portrait of a bold, brave, human Kennedy, once again a hero.
Growing Up -- Beginnings -- Privileged Youth -- The Terrors of Life -- Public Service -- Choosing Politics -- The Congressman -- The Senator -- Can a Catholic Become President? -- Nomination -- Election -- The President -- The Torch Is Passed -- The Schooling of a President -- A World of Troubles -- Crisis Manager -- Reluctant Warrior -- The Limits of Power -- Frustrations and "Botches" -- To the Brink--And Back -- New Departures: Domestic Affairs -- New Departures: Foreign Affairs -- An Unfinished Presidency.
Includes bibliographical references (pages 805-811) and index.
Keywords: Kennedy, John F. -- 1917-1963.; Presidents -- United States -- Biography; Biography